Arab Responses to Fascism and Nazism : Attraction and Repulsion - Gershoni, I. (Book collections on Project MUSE., 2014)
This is the first book to present an analysis of Arab response to fascism and Nazism from the perspectives of both individual countries and the Arab world at large. This collection problematizes and ultimately deconstructs the established narratives that assume most Arabs supported fascism and Nazism leading up to and during World War II. Using new source materials taken largely from Arab memoirs, archives, and print media, the articles reexamine Egyptian, Syrian, Lebanese, Palestinian, and Iraqi responses in the 1930s and throughout the war. While acknowledging the individuals, forces, and organizations that did support and collaborate with Nazi Germany and fascist Italy, Arab Responses to Fascism and Nazism focuses on the many other Arab voices that identified with Britain and France and with the Allied cause during the war. The authors argue that many groups within Arab societies - elites and non-elites, governing forces, and civilians - rejected Nazism and fascism as totalitarian, racist, and, most important, as new, more oppressive forms of European imperialism. The essays in this volume argue that, in contrast to prevailing beliefs that Arabs were de facto supporters of Italy and Germany - since "the enemy of my enemy is my friend"--Mainstream Arab forces and currents opposed the Axis powers and supported the Allies during the war. They played a significant role in the battles for control over the Middle East. Israel Gershoni is a professor in the Department of Middle Eastern and African History and Kaplan Chair for the History of Egypt and Israel at Tel Aviv University. He is the author of Dame and Devil: Egypt and Nazism, 1935-1940, volumes 1 and 2, and coauthor (with James Jankowski) of Confronting Fascism in Egypt: Dictatorship versus Democracy in the 1930s